A Peran Public Relation dalam Meningkatkan Citra Universitas Medan Area - Zebua, Ajniver Hamnur (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research is to examine how the role of public relations in improving the image of the University of Medan Area. In this study, the authors used field research (field research) which is qualitative in nature. Based on the conclusion, the researcher draws the conclusion that the strategy carried out by Public Relations in improving the image of the campus is by means of; Improving the quality of learning (lectures and practicum) and the quality of graduation and Improving the quality of the academic atmosphere.